2010
DOI: 10.1124/jpet.110.166488
|View full text |Cite
|
Sign up to set email alerts
|

A Long-Acting Tumor Necrosis Factor α-Binding Protein Demonstrates Activity in Both In Vitro and In Vivo Models of Endometriosis

Abstract: Endometriosis is characterized by the presence of elevated proinflammatory cytokines such as tumor necrosis factor (TNF) ␣ in the peritoneal cavity. Blocking interaction of TNF␣ with its receptor by the addition of excess TNF␣-binding protein (TBP)-1 (a soluble form of TNF receptor-1) was effective in animal models of endometriosis. Recently, a novel, high-affinity inhibitor of TNF␣, TNF-soluble high-affinity receptor complex (TNF-SHARC), was created by fusing TBP to both the ␣ and ␤ subunits of inactive human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 36 publications
0
17
1
Order By: Relevance
“…In contrast to the earlier study in rat endometriosis, 36 where Antide and TBP-1 showed no effect on NK cell activity, bentamapimod was able to reverse the effect of decreased NK cell cytotoxicity in endometriotic animals similar to earlier reports in mice 47 and human. 48 Reduced NK cell activity was observed in women with endometriosis.…”
Section: Discussioncontrasting
confidence: 49%
“…In contrast to the earlier study in rat endometriosis, 36 where Antide and TBP-1 showed no effect on NK cell activity, bentamapimod was able to reverse the effect of decreased NK cell cytotoxicity in endometriotic animals similar to earlier reports in mice 47 and human. 48 Reduced NK cell activity was observed in women with endometriosis.…”
Section: Discussioncontrasting
confidence: 49%
“…suggested that the production of IL‐8 by the endometrial stromal cells is also stimulated by proinflammatory IL‐1 and TNF‐α and IFN‐γ, characteristic for the inflammatory response induced by endometriosis. Altan et al . as well as Grund et al .…”
Section: Il‐8 and Endometriosismentioning
confidence: 92%
“…Vitamin E is a lipid-soluble, chain-breaking antioxidant that prevents the propagation of lipid peroxidation by forming a vitamin E radial [42, 43]. Vitamin C is generally recommended to be included along with Vitamin E supplementation since vitamin C helps in the recycling of Vitamin E radical back to Vitamin E [44]. We chose the stated concentrations because of clinical trials on cardiovascular diseases that used these levels [45] and our own unpublished studies suggested that at these concentrations they were nontoxic and decreased inflammatory markers.…”
Section: Methodsmentioning
confidence: 99%